La economía en el desarrollo de la Directiva Marco del Agua - La Roca, Frances; Ferrer, Graciela (Observatorio Medioambiental, 2007)
The European policy for sustainable development envisages a high degree of protection of the environment and the human health, as a part of social welfare, compatible with a sound economy. The possibility of maintaining economic growth with decreasing environmental pressure, the so called decoupling, is central in the attempt of making compatible environmental and economic objectives. Decoupling claims for a new way of understanding economic relations, in which the material dimension of the economy is much more relevant than in traditional economics. As a consequence, also new policy instruments emerge. The paper discusses the use of economic analysis and instruments in the implementation of the European Water Framework Directive, focusing on the incoherencies that a weak conceptual approach can introduce in practice.